Josquin Desprez’s Mass in the music of Georg Friedrich Haas: dynamic of the past as the present-day model - Chornyi, Oleksandr (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the article is to consider chamber music of Austrian composer Georg Friedrich Haas as an example of the dynamic interaction of the composer's practice of Renaissance and contemporary classical music. The author's methods of temporal and spatial organization, as well as aesthetic and ideological markers of Georg Friedrich Haas in his rework of the historical material — the Mass “L'homme armé super voces musicales” by the Flemish composer Josquin Desprez — are studied and classified. The research relies on methods of complex analysis to determine the elements of interaction with the original material and its composer's processing, during which the sound resources, composition techniques, and the essence of Haas's spectral and microtonal system in practice are highlighted. Main objective of the study is to identify dynamic processes in the music of Georg Friedrich Haas on the example of the work “Tria ex Uno” for ensemble (2001), which combines the practices of ancient and contemporary music. The scientific novelty of the article is based on the coverage of innovative methods of dynamic interaction between a contemporary composer and musical material of the past. The methodology includes the analysis of dynamic markers and their deployment in the time-space of Haas's work, using the method of comparison (to compare the music of Haas and Joaquin Desprez and to identify those elements that have been reworked / recycled in the contemporary work), generalization (for modeling the dynamic processes that occur in the integral system of interaction between composer-performer-hearer), content analysis, as well as historical, biographical and source studies. Results and conclusions. The study examines the composer's strategies of working with historical material, which show an unprecedented level of detail in interaction not only with aspects of pitch or polyphonic structures, but also with the ideological and aesthetic dynamics of the past, which is reactualized in the context of the present. The emergence of new compositional techniques, technological evolution, allowed the composer to rework, improve, or significantly expand the functions of the original work, in which Despres' splitting of time into three gradations becomes Haas' multi-parameter splitting of micro- and macro-time, and the detailed polyphony of the material evolves into microscopy of individual sounds and work with their “beatings” (Schwebungen). Of particular scientific interest is the way Haas works not only with the time-space of the work, but also with the very function of music and the institution of authorship. In this context, the dynamism of the abstract author is manifested, realizing the phenomenon of counterfeiting and double borrowing: borrowing a work that is already a borrowing. The article discusses various aspects of counterfeiting, the importance of the conscious use of counterfeits and their positive impact on the development of contemporary music.